2021
DOI: 10.1007/s10722-021-01200-w
|View full text |Cite
|
Sign up to set email alerts
|

The trauma of no-choice: Wild food ethnobotany in Yaghnobi and Tajik villages, Varzob Valley, Tajikistan

Abstract: Due to global change and the migration crisis both needing rapid attention, there has been growing debate about the drivers of change in the diet of migrants. Our study aimed to evaluate the consequences of forced resettlement on local ecological knowledge related to wild food plants among forcefully resettled Yaghnobi people in Tajikistan. We conducted 49 semi-structured in-depth interviews and recorded 27 wild food taxa and five unidentified folk taxa used by Yaghnobis and Tajiks in the villages surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In this respect, there is a cultural and social continuity between the present events and the migratory phenomena that occurred during the twentieth century, which changed the geography of Europe, especially in mountain areas [ 7 9 ]. Migration is thus a key force in terms of the transformation of a community’s relationship with its surroundings, as well as with its local ecological knowledge (LEK) [ 10 13 ]: a change that cannot be described only in terms of opposition between tradition and modernity or between rural and urban [ 14 ], and not only in terms of sociocultural erosion [ 15 ]. In so far as LEK is situated knowledge [ 16 ], the analysis of rural migration raises questions concerning the spatial reorientation and cultural adaptation of local communities.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, there is a cultural and social continuity between the present events and the migratory phenomena that occurred during the twentieth century, which changed the geography of Europe, especially in mountain areas [ 7 9 ]. Migration is thus a key force in terms of the transformation of a community’s relationship with its surroundings, as well as with its local ecological knowledge (LEK) [ 10 13 ]: a change that cannot be described only in terms of opposition between tradition and modernity or between rural and urban [ 14 ], and not only in terms of sociocultural erosion [ 15 ]. In so far as LEK is situated knowledge [ 16 ], the analysis of rural migration raises questions concerning the spatial reorientation and cultural adaptation of local communities.…”
Section: Introductionmentioning
confidence: 99%
“…On the Pakistani side, we mainly relied on own research work [ 8 , 9 , 10 ], while for the Afghan Pamir we found only a single study which recorded the ethnobotanies of the Kyrgyz and Wakhi peoples [ 11 ]. Similarly, we also compared the data with our research conducted in Tajikistan in the past year [ 15 ]. In addition, we considered other medicinal ethnobotanical studies [ 12 , 13 , 14 , 16 ] in order to have a comprehensive comparative analysis to establish the novelty of our results.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we found some ethnobotanical studies which recorded medicinal plant uses from the Tajik and Afghan Pamirs [ 12 , 13 , 14 ]. In Tajikistan, our research group has conducted a wild food ethnobotanical study in the Varzob Valley [ 15 ]. Similarly, the ethnobotanical study of medicinal teas from Southern Xinjiang, China is an important contribution to the field of the ethnobotany of mountain regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…While in the modern world, especially in industrialized parts, wild food plants have shifted to the periphery of food systems, though they still constitute a reservoir of healthy food, especially when food supplies are disrupted [ 4 ]. Therefore, they have recently become a widespread research topic [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the use of plants has historically been acquired through trial and error and subsequently circulated through oral and written communication between generations, keeping use associated with local flora. Wild plants constitute a significant food resource, especially in places highly vulnerable to climate change or military conflicts, although displacements of people erode local ecological knowledge which negatively contribute to food security [ 7 , 8 , 9 ]. Wild food plants were occasionally promoted in Europe during World War II (WWII) (see, for example, Finland [ 10 ], Norway [ 11 ]), yet after this time of hardship, the propagation of wild food plants in post-war Europe has been uncommon.…”
Section: Introductionmentioning
confidence: 99%